Legal Liability for Companies Regarding the Prohibition of Worship for Workers - Said Saleh; Sherin Audia Maharani; Sania Faridha Farasanti; Irma Maulida; Deni Yusup Permana (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study discusses the prohibition of worship for workers in beauty companies around Cirebon Regency based on labor laws in Indonesia. Freedom of worship is a basic right of every human being guaranteed by the 1945 Constitution and Law Number 13 of 2003 concerning employment. However, there are still companies that limit their workers to worship, as happened in the city of Surabaya. The same thing also happened in one of the cosmetics companies around Cirebon Regency, Company X. This paper uses normative juridical methods, with data from literature studies and interviews with several workers at Company X and the Manpower Office as our supporting data. This research is expected to provide insight for companies, legal practitioners, and the general public in understanding the rights and obligations of workers and the company's obligations to workers. The study's results show that company X's policies are contrary to regulations and can be considered discriminatory, adversely affecting employee welfare and company reputation. Legal consequences that can be imposed on companies include administrative sanctions, civil lawsuits, and criminal charges under applicable regulations. If the company does not have company regulations, it can be subject to criminal sanctions, including a fine of at least Rp.5,000,000 (five million rupiah) and a maximum of Rp.50,000,000 (fifty million rupiah).